2012
DOI: 10.1016/j.ssi.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-17 nuclear magnetic resonance measurements on apatite-type lanthanum silicate (La9.33(SiO4)6O2)

Abstract: We used magic angle spinning (MAS), multiquantum (MQ)-MAS, and high-temperature (HT) nuclear magnetic resonance (NMR) measurements to investigate the oxide-ion conduction path of oxygen-17 (O-17) in apatite-type lanthanum silicate La9.33(SiO4)6O2. A highly crystalline apatite-type lanthanum silicate was specifically synthesized for the measurements. MAS and MQ-MAS NMR confirmed that four kinds of oxide-ion sites are present in the structure and showed a small extra peak (<1%) possibly due to an interstitial si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The latter assignment is consistent with the observation of interstitial O species in previously reported silicate-and germanate-based rare earth apatite SOFC materials. 47,49 It can be observed that upon dehydration of these systems both of these interstitial species are essentially removed, with the more complete removal of the Si-O-Si/Si-OH interstitial species being observed from the La 8 Sr 2 Si 6 O 26 system, suggesting that this component is mostly related to Si-OH (see Fig. 10(b)).…”
Section: Dalton Transactions Papermentioning
confidence: 95%
“…The latter assignment is consistent with the observation of interstitial O species in previously reported silicate-and germanate-based rare earth apatite SOFC materials. 47,49 It can be observed that upon dehydration of these systems both of these interstitial species are essentially removed, with the more complete removal of the Si-O-Si/Si-OH interstitial species being observed from the La 8 Sr 2 Si 6 O 26 system, suggesting that this component is mostly related to Si-OH (see Fig. 10(b)).…”
Section: Dalton Transactions Papermentioning
confidence: 95%
“…Despite the very low inherent receptivity of 17 O SSNMR spectroscopy, there is a sizable body of high-quality work; the reader is directed toward several comprehensive reviews of the field. There has recently been significant progress in 17 O SSNMR, including the development of 17 O dynamic nuclear polarization (DNP) SSNMR spectroscopy. 17 O SSNMR has been used to investigate the structure and disorder in variety of glasses, along with water, ice, hydrated compounds, and clathrate hydrates. This technique has been applied across very diverse chemical fields, , including organic and biological molecules, ,,,,, drugs and pharmaceuticals, , and battery systems. , …”
Section: Introductionmentioning
confidence: 99%
“…Apparent exchange of O(1), O(2) and O(3) oxide ions bonded to Si was observed by 17 O NMR measurement on La 9.33 Si 6 O 26 by KIYINO et al [22], while it was not observed for oxide ion on the isolated site O(4). The results indicate that oxide ions bonded to Si at the position O(1), O (2) and O(3) are the main diffusion species in the oxide ion conductivity.…”
Section: Apatite-type Lanthanium Silicatesmentioning
confidence: 94%